Exploring The Two Decades Of Quality Assurance Advancement In Vocational Education And Training - Ramadhan, Muhammad Oka; Rohendi, Dedi; Handayani, Mustika Nuramalia; Permana, Asep Yudi (JIV-Jurnal Ilmiah Visi, 2023)
Quality assurance in vocational education and training (VET) becoming a concern driven by evolving educational landscapes and the demand for skilled and job-ready individuals. This study presents a comprehensive bibliometric analysis of research on VET quality assurance from the year 2003 to 2022. Data was visualized using VOSviewer and Tableau. This paper aims to provide insights into the quantitative distrubution, citation pattern, geographical dispersion, and emerging topics in this field. Results show an increasing volume of publications on quality assurance in VET. The citation pattern suggests that the depth of exploration and engagement with existing knowledge is not proportionally robust. Russian Federation emerges as a prominent contributor in terms of document output. A lack of international research collaboration among countries, signaling a need for increased global engagement. The identified trends in research can be categorized into three clusters. Cluster 1 focuses on aspects related to the implementation of quality assurance in VET, Cluster 2 delves into methodological approaches in this context, and Cluster 3 explores research contexts associated with the value, benefits, or objectives of implementing quality assurance in VET. This article also offers a reflection on the findings as research that necessitates further exploration. This article can serve as a valuable resource for empirical researchers seeking to examine the temporal evolution of study participants and the shifting research themes pertaining to quality assurance in vocational education.